Exploration on sulfur/acid treatment of sepiolite composite positive electrode material for lithium-sulfur battery. Issue 1 (1st January 2021) - Kalaiselvi, C.; Krishnaveni, K.; Priyanka, V.; Rajkumar, P.; Subadevi, R.; Sivakumar, M.
Abstract: High energy density battery system is endowed with more complex Lithium sulfur cathode whose electrochemical redox reaction and phase transition occurred due to multi electron participation. The different mole ratios of sepiolite mixed with sulfur were synthesized by acid cum thermal treatment method. The morphological analysis illustrates that the sepiolite powder is composed of micro fibrous bundles in the range of 1 μm to 10 μm. The sorption isotherms indicate that the sieved sepiolite (Sp) and different mole ratio (4, 6 and 8) of sepiolite/sulfur shows a type-IV isotherm of mesoporous material. The S/SvSp (sulfur/sieved sepiolite) composite cathode exhibits an initial discharge capacity of 1066 mAh g −1 and attains a stable capacity of 596 mAh g −1 during 40 cycles with 97% of efficiency. All the results correlated with the better electrochemical behaviour of electrode and it satisfies the needs of high energy density storage application. Highlights: Different moles of acid treatment of sieved sepiolite/sulfur were prepared by heat treatment method. Effect of micro-/mesoporosity of pre-treated sep/S for improved Li–S battery. The mesoporous nature of materials helps to reducing the polysulfide dissolution. The sepiolite coated Sulfur particles have the six tens of nanometer in size.